2015
DOI: 10.1007/s10549-015-3456-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between breast cancer and thyroid cancer: a meta-analysis

Abstract: Previous studies have suggested an association between breast cancer and thyroid cancer; however, there has not been a formal meta-analysis which collates the existing evidence supporting the hypothesis that breast cancer or thyroid cancer predisposes an individual to developing the other. A systematic search was carried out using PubMed and Medline. We searched for articles containing epidemiological evidence of breast cancer following thyroid cancer and vice versa. Additionally, we searched for articles that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 42 publications
10
54
0
Order By: Relevance
“…The β TC and β BC values, which provide a quantitative assessment of the magnitude of the TC-BC association, were found to be practically identical, as should be expected, since both coefficients refer to the same TC-BC association. The result of Eqs (9, 10) further support the spatiotemporal co-existence of TC and BC incidence distributions at the population level, according to the IDP criterion, and are in agreement with some earlier findings suggesting the co-existence of TC and BC diseases17394041.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The β TC and β BC values, which provide a quantitative assessment of the magnitude of the TC-BC association, were found to be practically identical, as should be expected, since both coefficients refer to the same TC-BC association. The result of Eqs (9, 10) further support the spatiotemporal co-existence of TC and BC incidence distributions at the population level, according to the IDP criterion, and are in agreement with some earlier findings suggesting the co-existence of TC and BC diseases17394041.…”
Section: Resultssupporting
confidence: 89%
“…Indeed, several researchers have suggested that due to common risk factors there may exist a strong association between TC and BC incidence4041.…”
mentioning
confidence: 99%
“…Familial PTC may occur in combination with other Mendelian cancer syndromes (familial adenomatous polyposis, Gardner’s syndrome, Peutz-Jeghers syndrome, and Cowden’s syndrome) or may be unassociated with other neoplasms in familial aggregates. However, although the risk of developing extra-thyroidal malignancy in non-Cowden’s syndrome is documented [21,22], the clinical correlation between sporadic breast cancer (20% of which are HER2+ ) [23] and PTC is still controversial [24,25], and the co-occurrence of both disorders in the same individual is a subject of extensive debate [26,27]. None of our fPTC patients had clinical or pathological evidence of hereditary syndromes associated with NMTC, breast cancer, or other types of sporadic tumors, except for one male patient who had a previous squamous cell carcinoma of the auricle.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians may propose that patients with thyroid cancer perform breast self-examinations periodically and undergo ultrasonic mammography regularly. It has been reported that there is an association between breast cancer and thyroid cancer; this association may be attributable to common etiologic features, pathologic processes, or treatment-related factors (27,28) that these 2 cancers share. Previous studies suggested the relationship between serum levels of thyroid hormones or thyroid peroxidase autoantibodies and the risk or prognosis of breast cancer (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%